EVALUATION OF CARDINAL TEMPERATURES AND THERMAL TIME REQUIREMENT FOR GERMINATION OF SCROPHULARIA STRIATA AND TANACETUM POLYCEPHALUM (SCHULTZ BIP. SSP. HETEROPHYLLUM) - Karavani, Bahram; Afshari, Reza Tavakkol; Hosseini, Nasser Majnoon; Moosavi, Seyed Amir; Akbari, Hamed (Plant Breeding and Seed Science, 2018)
Scrophularia striata and Tanacetum polycephalum are important medicinal plants in Iran which are rich in essential oils, bitter substances, and sesquiterpene lactones. The present study was conducted to compare four non-linear regression models (segmented, beta, beta modified and Dent-like) to describe the germination ratetemperature relationships of Scrophularia striata and Tanacetum polycephalum over eight and seven constant temperatures, respectively, to find cardinal temperatures and thermal time requirements to reach different germination percentiles. An iterative optimization method was used to calibrate the models and different statistical indices including RMSE, coefficient of determination (R2), and AICc were applied to compare their performance. The beta model was found to be the best model to predict germination rate of Scrophularia striata at D10, D50 and D90 (R2 = 0.96, R2 = 0.97, R2 = 0.95; RMSE = 0.005, 0.001 and 0.001, respectively). According to this model outputs, the base, optimum, and the maximum temperatures for germination were estimated as 1.21 ± 0.39, 25.91 ± 0.33 and 46.35 ± 4.12 °C, respectively. Also the segmented model was found to be the best model to predict germination rate of Tanacetum polycephalum at D10, D50 and D90 (R2 = 0.98, R2 = 0.98, R2 = 0.98; RMSE = 0.067, 0.59 and 0.56, respectively). According to the model outputs, the base, optimum, and the maximum temperatures for germination were estimated as 0.44±1.15, 26.95±0.75 and 38.33±0.98 oC, respectively. It seems these two medicinal plants need moderate optimum temperature for seed germination.